(untitled) (American Journal of Islam and Society, 2007)
There is a striking lack of studies on the Palestinian diaspora. Undoubtedly the pioneering work of Edward Said (“Reflections on Exile,” in Out There: Marginalization and Contemporary Cultures, eds. Russell Ferguson [The MIT Press: 1990]) on exile and Rashid Khalidi (Palestinian Identity: The Construction of Modern National Consciousness [Columbia University Press: 1997]) both touch on many of the related issues of collective memory, cultural identity, and the relationship between the “center” (the homeland) and the diasporic communities and how these issues manifested themselves in the Palestinian case. More recently, Abbas Shiblak (Reflections on Palestinian Diaspora in Europe [2000]), Sari Hanafi (Here and There: Analyses of the Relationship between Diaspora and the Centre [2001: in Arabic]), and Helena Schulz and Juliane Hammer (The Palestinian Diaspora: Formation of Identities and Politics of Homeland [Routledge: 2003]) explore different aspects of the Palestinian diaspora. Juliane Hammer’s new study examines young Palestinian returnees as part of a larger social, historical, political, and cultural framework (p. 114). She conducted her research in the mid-1990s, a crucial period between two phases: one of peace and hope following the signing of the Declaration of Principles in 1993, and another one that started in 1997 with the deterioration and breakdown of the peace talks, and, consequently, with the eruption of the second Intifada in 2000. For her survey, she chose a sample of two main categories of young returnees: those of the Palestinian Authority strata (a`idin) and the children of Palestinian expatriates who live in the West but mainly in the United States (Amerikans). The interviewees were mainly adolescent or young men and women from and around Ramalla and Jerusalem. The return process has been described chronologically, as a series of five steps or stages ranging from the decision to return to plans for the near future. As the study argues, this return entails a process of the returnees’ rewriting aspects of their identities. Hammer does not see, however, that the chronological approach is the only way of looking at the process of return. She sees the transformation (what she calls the “rewriting of identities”) also by dividing “identity” into different aspects, and then investigating how the respondents remembered these aspects from their childhood and youth in the ...